Characteristics, Treatment, Outcomes, and Survival in Neuroendocrine G1 and G2 Pancreatic Tumors: Experiences From a Single Tertiary Referral Center - Jan Calissendorff; Jan Calissendorff; Freja Bjellerup-Calissendorff; Freja Bjellerup-Calissendorff; Robert Bränström; Robert Bränström; C. Christofer Juhlin; C. Christofer Juhlin; Henrik Falhammar; Henrik Falhammar (Frontiers in Endocrinology, 2021)
PurposeNeuroendocrine tumors of the pancreas (Pan-NETs) are usually hormonally inactive with a capacity to metastasize. Since Pan-NETs are rare, more knowledge is needed.MethodsWe reviewed all patients’ medical files with Pan-NET treated at a tertiary center (2006-2019). Grade 1 (G1) and grade 2 (G2) tumors were compared. The latter group was subdivided arbitrarily based on proliferation index into G2a (3-9.9%) and G2b (10-19.9%).ResultsWe found 137 patients (76 females, 61 males; G1 n=66, G2 n=42), the median age at diagnosis 61 years (interquartile range (IQR) 50–71), and tumor size 2 cm (1.3–5 cm). The initial surgery was performed in 101 patients. The remaining (n=36) were followed conservatively. Metastatic disease was evident in 22 patients (16%) at diagnosis while new lesions developed in 13 out of 22 patients (59%). In patients without previous metastatic disease, progressive disease was discovered in 29% of G1 vs. 55% of G2 patients (P=0.009), 47% of G2a vs. 75% of G2b patients (NS). Survival was poorer in patients with metastasis at diagnosis vs. those with local disease (P<0.001). During follow-up of 74 months, Pan-NET related death was found in 10 patients. Survival was not different between G1 vs. G2 or G2a vs. G2b, or if tumors were functional. Size ≤2 cm was associated with a better outcome (P=0.004). During the follow-up of small tumors (≤2 cm, n=36) two were resected.ConclusionIn small non-functional Pan-NETs, active surveillance is reasonable. Progressive disease was more common in G2, but survival was similar in G1, G2 and between G2 subgroups. Survival was poorer in patients with metastasis at diagnosis.